Ex Libris Jana Wiktora / [Stanisław Jakubowski]. - Jakubowski, Stanisław (1885-1964) ([wydawca nieznany], 1928)
W obramowaniu leżąca księga, napis u góry: Ex Libris, u dołu: Jana Wiktora. Sygnatura artysty w obrębie kompozycji.